Geochemical Characteristic of the Carbonaceous Sediments of the Upper Paleozoic Kuantan Group, Malaysia - Burgan, Amer (MO.RI Publishing, 2024)
The geochemical parameters discussed in this paper are based on the analysis of twelve outcrop carbonaceous samples, mainly black shales, using X-Ray Fluorescence (XRF) and Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) techniques. These samples are representative of the Charu, Sagor, and Permian formations. The aim of this study is to define and discuss their characteristics, the distribution abundance of major and minor elements, investigate the dominant mineralogical composition, and reconstruct the depositional environment for these sediments. The bulk chemical results showed that the average values of the major elements are 65.83%, 64.82%, and 71.4% SiO?; 18.27%, 22.2%, and 15.66% Al?O?; 1.53%, 0.99%, and 2.49% Fe?O?; and 4.06%, 6.25%, and 3.66% K?O for the Charu, Sagor, and Permian formations, respectively. The minor elements recorded values of 524.4 ppm, 758.8 ppm, and 446.3 ppm Ba; 366 ppm, 399.3 ppm, and 257.3 ppm Rb; 88 ppm, 67.3 ppm, and 47.3 ppm Sr; and 308 ppm, 288.8 ppm, and 327 ppm Zr for the Charu, Sagor, and Permian formations, respectively. The major oxides reflect the dominant mineralogical composition of quartz and other silicate minerals (e.g., illite, kaolinite, smectite) and a deficiency in carbonates. The high Rb/K ratio suggests a brackish marine environment or rapid deposition that prevented equilibrium between Rb and K in these shales. The high Rb/Sr ratios of 4.16, 5.89, and 5.44 for the Charu, Sagor, and Permian formations, respectively, are possibly attributed to the low Sr content due to reducing conditions prevailing during the deposition of these sediments.